Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

Senior Safety Plan : Raising Awarness of Elder Abuse on the Lower North Shore - Maurice, Jenna; Kippen, Kayla (Coasters Association, 2022)

World Elder Abuse Awareness Day : Well-Treatment in All Circumstances - Michaud, Julie (2021)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2009)

A Study of Women's Needs on the Lower North Shore - Keats, Shannon A. (Coasters Association, 2006)
The mission of the Coasters Association is to develop knowledge of the needs and expectations of the fourteen (14) communities on the Lower North Shore, and act in partnership with community leaders, organizations and stakeholders to design and deliver community strategies, programs and services which respond to the region’s development challenges. In keeping with their mission and providing an opportunity to better the situation of women on the Lower North Shore, a project entitled “A Study of the Needs of Women on the Lower North Shore”, was initiated. The project began on the September 12th, 2005 and ended on March 31st, 2006 (29 weeks). The key goal of the project was to get women involved and talk about the issues facing them and to identify opportunities and lasting solutions, as well as make women aware of the programs and services that are available on the coast, through partnerships with other organizations and to help these women make use of those programs. The purpose of the project was to research information through means of a questionnaire and by organizing focus groups to develop a needs assessment and to establish a coalition (for Phase 2 of the project) to improve the overall status of women on the Lower North Shore of Quebec.

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1989)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1987)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1986)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1985)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1984)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1984)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1983)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1981)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1979)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1978)

Racism and Conjugal Violence - Black Community Resource Centre (BCRC)

The Many Faces of Elder Abuse - Voice of English-speaking Quebec (VEQ)
Voice of English-speaking Québec is proud to support English-speaking seniors in the greater Quebec City region. This booklet was produced to help seniors in our community stay independent, safe and to help prevent abuse and discrimination targeting them. This project is funded in part by Service Canada under the New Horizons for Seniors Program.